2006
DOI: 10.1021/la062007l
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Controlled Cell Adhesion via Micropatterned Surface Modification of Poly(dimethylsiloxane)

Abstract: Spatial control of cell growth on surfaces can be achieved by the selective deposition of molecules that influence cell adhesion. The fabrication of such substrates often relies upon photolithography and requires complex surface chemistry to anchor adhesive and inhibitory molecules. The production of simple, cost-effective substrates for cell patterning would benefit numerous areas of bioanalytical research including tissue engineering and biosensor development. Poly(dimethylsiloxane) (PDMS) is routinely used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 31 publications
3
63
0
Order By: Relevance
“…For SAM/sp-Co-Cr, the peaks observed at [8]. In the literature, the BE of Si 2p peak at $102 eV was assigned to Si-O-Si cross-links [65][66][67][68][69] and the peak at $102.6 eV BE was assigned to Si-O-Metal linkages [65,69,70]. In our study, the BE of Si 2p was observed at 102.…”
Section: Formation and Characterization Of Ots Sam On Co-cr Alloysupporting
confidence: 59%
“…For SAM/sp-Co-Cr, the peaks observed at [8]. In the literature, the BE of Si 2p peak at $102 eV was assigned to Si-O-Si cross-links [65][66][67][68][69] and the peak at $102.6 eV BE was assigned to Si-O-Metal linkages [65,69,70]. In our study, the BE of Si 2p was observed at 102.…”
Section: Formation and Characterization Of Ots Sam On Co-cr Alloysupporting
confidence: 59%
“…22 Our work confirms other findings where endothelial cells have been shown to be partially excluded from hydrophobic surfaces in favor of hydrophilic surfaces due to a reduced adhesion on hydrophobic surfaces. 8,25 Furthermore, others have shown a decrease in cell viability/density on hydrophobic glass, 8 which we also confirm. The resulting impact that we show on the degree of confluence of the cells was a 10-fold increase in confluence by only providing a hydrophilic vs. hydrophobic bare glass substrate both in culture and in the bioassay chamber.…”
Section: Bare Hydrophilic Vs Hydrophobic Glasssupporting
confidence: 85%
“…The significantly higher cell density within the patterned regions is thus likely due to a combination of factors, including the probable inability for cells to adhere to hydrophobic surfaces. 22,25,26 Within the ECM stamped areas, the higher density could have been due to either an increase in initial endothelial cell attachment to ECM proteins, 6,19 although where cells initially land is partly due to statistical probably. Despite this, others have shown an increased ability to direct cells onto patterned collagen IV onto hydrophobic glass coverslips because the cells had an increased ability to initiate attachment to collagen IV.…”
Section: Cell Density and Confluencementioning
confidence: 99%
“…Due to the low surface energy and hydrophobicity, PDMS surfaces inhibit cell adhesion (Patrito et al 2007). However, a good adhesion is obtained between PDMS and polished surfaces like tissue culture polystyrene plate (TCPS) and glass (Lotters et al 1997).…”
Section: Introductionmentioning
confidence: 99%